The Impact of Liquidity Risk & Market Risk on the Profitability of Banking Companies - Raprayogha, Rusdi; Abdullah, Wahidah; Anugrah, Nurfahri Ramadhan (Study of Scientific and Behavioral Management, 2021)
Banks have a very important and strategic role in supporting national economic development. As a financial service institution, one of the real roles of banks is in channeling funds to people who need business capital through micro, small and medium enterprises. Banks are also an industry capable of turning savings into investments. With this strategic function, it is not surprising that banks receive great attention from the government, because banks are a business that is full of risks that occur in the banking system and can have a fatal impact on the economy as a whole. This research is a type of quantitative research. The population in this study were all financial statements of banking companies listed on the Indonesia Stock Exchange for 5 years from 2013 to 2017. The research sample was determined by purposive sampling method. The analysis technique used in this research is multiple linear regression analysis. The results showed that simultaneously the liquidity risk variable, market risk had a significant impact on profitability, and partially the liquidity risk variable had a significant and negative impact on profitability, while the market risk variable had a significant and positive impact on profitability. Based on the results of this research, it can be concluded that the higher the liquidity risk, which is reflected in the LDR, can result in decreased profitability. On the other hand, the higher the LDR indicates a high level of credit but is not followed by a high rate of return (bad credit), so that the bank experiences losses or decreases in profitability. In addition, it shows that when there is an increase in risk in the market, the market will tend to shift its assets to the banking sector which is then considered safer.